Preparation of wafer-scale highly conformalamorphous hafnium dioxide thin films by atomic layer deposition using a thermally stable boratabenzene ligand-containing hafnium precursor - Ansari, Mohd Zahid; Janíček, Petr; Park, Ye Jin; NamGung, Sook; Cho, Bo Yeon; Nandi, Dip K; Jang, Yujin; Bae, Jong-Seong; Hong, Tae Eun; Cheon, Taehoon; Song, Wooseok; An, Ki-Seok; et al. (Elsevier Science BV, 2023)
In the present study, HfO2 thin films were fabricated via atomic layer deposition (ALD) using a novel heteroleptic metal organic precursor [tris (dimethylamino) dimethylaminoboratabenzene hafnium] [eta(6):eta(1)-(C5H5BNMe2)Hf (NMe2)(3); (BBHf)] along with O2 as the oxygen source at a range of growth temperatures (i.e., 150-350 degrees C). This novel precursor is a heteroleptic complex synthesized by the introduction of a boratabenzene ligand (BB) into the parent Hf metal sphere to achieve an enhanced thermal stability. In this system, O2 is used as a mild oxygen-containing reactant to replace the typically employed ozone (O3). Distinctive self-limiting deposition was established with a comparatively high growth per cycle value of 0.068 nm, and linear growth was observed as a function of the ALD cycle number. Thermal decomposition was not detected at or below 350 degrees C, thereby indicating the improved thermal stability compared to when frequently used Cp (cyclopentadienyl)-amide precursors are employed. Under the ALD deposition conditions employed herein (275 degrees C), a complete step coverage was achieved with a good conformality on high aspect ratio dual trenches [top and bottom widths = 40 and 15 nm, respectively, aspect ratio (AR) approximate to 6.3], and uniformity was obtained on the large planar substrate (15 cm diameter). Upon annealing at 700 degrees C, the as-grown film formed an amorphous structure with a slightly enhanced crystallinity, while annealing at 850 degrees C led to the generation of nanocrystalline HfO2 films with amorphous structures, as indicated by X-ray diffraction measurements. The as-grown films were determined to be slightly rich in oxygen compared to the stoichiometry of HfO2, although they also contained significant amounts of residual impurities, such as H, B, and C (similar to 6, 6, and 7 at.%, respectively), as confirmed by Rutherford back-scattering spectrometry and elastic recoil detection analyses. The impurity levels were further reduced by increasing the growth temperature and by subsequent post-annealing, as evidenced by X-ray photoelectron spectroscopy and secondary-ion mass spectrometry analyses. Finally, ellipsometry analysis was performed to measure the optical properties of the prepared ALD-HfO2 thin films. It is expected that the described process may be of significance in the preparation of high-k films wherein thermally stable amorphous films with extremely conformal and uniform coatings are required to fabricate next-generation electronic devices.
Příprava vysoce konformních tenkých filmů amorfního oxidu hafničitého pomocí depozice atomární vrstvev za použití tepelně stabilního prekurzoru hafnia obsahujícího boratabenzenový ligand pokrývajících velké plochy
Keywords: Amorphous hafnium dioxide; Thin films; Atomic layer deposition; Boratabenzene ligand; Wafer-scale films; Amorfní oxid hafničitý; Tenké filmy; Depozice atomových vrstev; boratabenzenový ligand; pokrytí velkých ploch